FOODPAIRING AND INNOVATIVE FOOD TECHNOLOGIES: ALGORITHMISATION OF FLAVOUR COMBINATIONS IN HORECA - BUDNYK, NINA; MOROZ, SVITLANA; KALASHNYK, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article explores the conceptual foundations of implementing foodpairing methodology in HoReCa establishments, focusing on the algorithmization of flavor combinations through molecular analysis, sensory science, and digital technologies. Foodpairing, rooted in the structural affinity of volatile aromatic compounds, represents a shift from intuitive culinary thinking to data-driven taste design. This approach enables HoReCa to systematically construct menus, minimize experimental risks, enhance quality predictability, and forge unique gastronomic identities. Traditionally, flavor pairings relied on cultural traditions and chefs’ experience, but today they increasingly depend on molecular profile databases, machine learning algorithms, and protocols for aroma enhancement, stabilization, or phasing during consumption. The integration of flavoromics, chemical and recipe databases, and social media analytics forms a new infrastructure for scientific verification of gastronomic combinations, as illustrated by a generalized model of foodpairing verification based on molecular interactions. Leading global market trends institutionalize foodpairing as a tool for research and development in the restaurant business and among food ingredient manufacturers. Suppliers create specialized compatibility maps, consulting firms analyze aroma connection graphs, and digital platforms provide chefs access to thousands of ingredient profiles. In practice, this manifests in harmonizational approaches (e.g., pairing cacao with fermented fruits) and contrastive ones (e.g., combining iodized notes with milky-caramel ones). Bar culture embodies this through methodical food-drink pairing, where courses are enhanced by cocktails with controlled acidity and texture. Technological flavorization is a key trend, involving micro- and nano-level encapsulation, controlled gelification, emulsions with calibrated dispersion, dehydration, lyophilization, liquid nitrogen application, and Maillard reaction control. These tools "package" aromas in carriers, regulating release rates to create multilayered temporal experiences. Algorithmization of decision-making is another axis of development, where machine learning analyzes aroma molecule databases, recipe corpora, guest feedback, and social media trends. This hybrid of sensory science and recommendation systems uncovers hidden compatibility spaces, accelerating prototyping in HoReCa. Personalization and gastronomic ethics gain prominence, addressing dietary restrictions, allergenicity, and clean-label demands, reducing enhancers, sugar, and salt without hedonic loss. Sustainable development adds dimension, utilizing undervalued byproducts for zero-waste menus where taste and ethics reinforce each other. Fermentation culture convergence is significant, generating rich volatile compound libraries as "aromatic bridges" for incompatible ingredients. Global restaurants establish fermentation labs where foodpairing guides design, controlling variables like temperature, water activity, pH, and microbiota. In Ukraine, war-induced disruptions catalyze interest in local raw materials, artisanal production, and embedded fermentation practices, leveraging seasonal berries, regional cheeses, pickling, kvass, and herbs for acid-terpene and phenolic profiles. This enables unique solutions without expensive imports, enhancing regional identity. Compared to international practices with commercial databases and R&D centers, Ukraine faces limitations: lack of open aroma profile libraries, limited lab equipment, insufficient interdisciplinary education, and economic sensitivity. Yet, strengths include deep-rooted fermentation traditions, seasonal harvesting, growing artisanal scene, and business adaptability, fostering competitive advantages on the global market. Successful Ukrainian cases rely on minimal sufficient science (public compound bases, staff sensory panels), technological discipline (process maps for stability), and narrative service (stories boosting hedonic evaluation). The market moves toward integrated smart kitchens where foodpairing is operational, syncing supply chains, aroma libraries, and service tempo. Functionalization integrates enriched ingredients like lactic ferments and prebiotic fibers, maintaining healthy profiles without taste compromises. Strategic challenges are scalability and efficiency, with global networks standardizing via centralized labs. For Ukraine’s SMEs, cooperative models – shared labs, equipment pooling, regional aroma banks, cluster purchases—lower entry barriers and accelerate knowledge accumulation. Comparative analysis (Ukraine vs. world) highlights infrastructure gaps but underscores local sustainability and adaptability as resources. The study substantiates foodpairing’s evolution from empirical art to scientific discipline, integrating microbiology, sensory science, and algorithms. In Ukraine, it leverages cultural heritage for authentic innovations. Future research should focus on consumer health impacts, AI-integrated platforms, and experimental studies combining sensory and molecular chemistry to define flavor harmony mechanisms, promoting personalized, healthy, and culturally authentic practices in HoReCa.